Crystal structure of (2-(1-hydroxyheptyl)octahydro-8aH-chromene-5,8,8a-triol), C16H30O5 - Wang Guangdi; Qian Shihao; Yan Sun; Wen Tingchi (Zeitschrift für Kristallographie - New Crystal Structures)
C16H30O5, monoclinic, P21 (no. 4), a = 5.6814(5) Å, b = 13.0181(12) Å, c = 22.833(2) Å, β = 96.473(2)°, V = 1677.9(3) Å3, Z = 4, R gt(F) = 0.0508, wRref (F 2) = 0.1346, T = 296(2) K.